Inactivation of Escherichia coli and Staphylococcus aureus by Ultrasound - SESAL, NÜZHET CENK (WILEY, 2014)
Objectives-The aim of this study was to obtain valuable information about the effect of ultrasonic irradiation with a frequency of 30 kHz frequency and power of 100 Won the inactivation capability of two bacterial groups, namely, Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923, in physiologic water samples. Methods-Ultrasonic irradiation of bacterial samples with different populations of 5 x 10(3), 1.5 x 10(4), and 3 x 10(4) colony-forming units/mL was performed at a constant frequency with various treatment times. The specific energy (gamma) values were calculated for these different concentrations of E coli and S aureus. The rate constant for ultrasonic inactivation was estimated in the linear region of a plot representing a survival ratio logarithm versus sonication time. Results-Although a significant death rate for E coli was observed with ultrasound treatment, in contrary to expectations, an increase in S aureus populations was observed. Conclusions-Considering the widespread use of ultrasound for sterilization of tools and equipment used in hospitals, the results obtained in this study indicate that ultrasonic irradiation is not a suitable method for the elimination of the major hospital pathogen S aureus.
Keywords: bacterial inhibition; specific energy; ultrasonic irradiation; DISINFECTION